PENGARUH MANAJEMEN LABA, AUDIT TENURE DAN KOMISARIS INDEPENDEN TERHADAP INTEGRITAS LAPORAN KEUANGAN - Karina Sucitra, (2021)
This research is a quantitative research that aims to analyze the influence of profit management, tenure audits and independent commissioners on the integrity of financial statements. The integrity of financial statements is proxyed by conservative indices using the Market to book ratio i.e. the value of the share price and the value of the equity book. This research uses sekunder data, which is an annual company of financial sector companies with banking sub-sectors listed on the Indonesia Stock Exchange for the period 2015-2018. The total sample studied was 160 samples using multiple linear regression models as a method of analysis with data processing tools spss. The results of this study prove that profit management has a significant negative effect, independent commissioners have a significant positive effect while tenure audits do not have the most influence on the integrity of financial statements.